Human, Nonhuman Primate, and Bat Cells Are Broadly Susceptible to Tibrovirus Particle Cell Entry - Caì, Yíngyún; Yú, Shuǐqìng; Jangra, Rohit K.; Postnikova, Elena N.; Wada, Jiro; Tesh, Robert B.; Whelan, Sean P. J.; Lauck, Michael; Wiley, Michael R.; Finch, Courtney L.; Radoshitzky, Sheli R.; O’Connor, David H.; et al. (Frontiers in Microbiology, 2019)
In 2012, the genome of a novel rhabdovirus, Bas-Congo virus, was discovered in the acute-phase serum of a Congolese patient with presumed viral hemorrhagic fever. In the absence of a replicating virus isolate, fulfilling Koch’s postulates to determine whether Bas-Congo virus is indeed a human virus and/or pathogen has been impossible. However, experiments with vesiculoviral particles pseudotyped with Bas-Congo glycoprotein suggested that Bas-Congo virus particles can enter cells from multiple animals, including humans. In 2015, genomes of two related viruses, Ekpoma virus 1 and Ekpoma virus 2, were detected in human sera in Nigeria. Isolates could not be obtained. Phylogenetic analyses led to the classification of Bas-Congo virus, Ekpoma virus 1, and Ekpoma virus 2 in the same genus, Tibrovirus, together with five biting midge-borne rhabdoviruses (i.e., Beatrice Hill virus, Bivens Arm virus, Coastal Plains virus, Sweetwater Branch virus, and Tibrogargan virus) not known to infect humans. Using individual recombinant vesiculoviruses expressing the glycoproteins of all eight known tibroviruses and more than 75 cell lines representing different animal species, we demonstrate that the glycoproteins of all tibroviruses can mediate vesiculovirus particle entry into human, bat, nonhuman primate, cotton rat, boa constrictor, and Asian tiger mosquito cells. Using four of five isolated authentic tibroviruses (i.e., Bivens Arm virus, Coastal Plains virus, Sweetwater Branch virus, and Tibrogargan virus), our experiments indicate that many cell types may be partially resistant to tibrovirus replication after virion cell entry. Consequently, experimental data solely obtained from experiments using tibrovirus surrogate systems (e.g., vesiculoviral pseudotypes, recombinant vesiculoviruses) cannot be used to predict whether Bas-Congo virus, or any other tibrovirus, infects humans.